Relevansi Sosiologis Pendidikan Islam di Era Disrupsi: Menakar Ulang Prinsip-Prinsip Tauhid dalam Arus Modernisasi dan Globalisasi (Jurnal Sosial Humaniora dan Pendidikan, 2025)
This article examines the relevance of Islamic education in addressing the challenges of the disruption era and globalization through the lens of modern social theories. Ideally grounded in the principle of tawhid and aimed at shaping holistic human beings, Islamic education is found to be insufficiently adaptive to social change, scientific advancement, and technological disruption. Utilizing a library research method, this study identifies philosophical and structural problems in Islamic education, such as the dichotomy of knowledge, outdated curricula, and weak integration of divine values with contemporary needs. By analyzing functionalism, conflict theory, and symbolic interactionism, the article argues for a redesign of Islamic education as a transformative, inclusive, and contextually grounded social system. It recommends a comprehensive reform of curricula, capacity building for educators, and integration of religious and scientific knowledge to reposition Islamic education as a meaningful agent of social change.